Rancang Bangun Sistem Informasi Umrah Terpadu Dengan Metode Iterative Enhancement - Fernandes, Billy; Farisi, Ahmad (Universitas Multi Data Palembang, 2025)
PT ABC Tour & Travel is a company specializing in Hajj Plus and Umrah travel services, headquartered in Tangerang with branches in Padang and Palembang. The company faces challenges in data management, particularly in pilgrim registration, package management, employee data, referrals, facilities, and company information. Manual data processing increases the risk of data loss, input errors, and inefficiency. This study aims to develop a web-based management information system using the Laravel framework, accessible by the Head Office, employees, as well as Branch Directors and staff. Implementing the Iterative Enhancement Model, the system includes features for recruitment, pilgrim registration, package management, employee data, referrals, facilities, document management, and company information. The system enhances data accuracy and operational efficiency, ensuring a more reliable and streamlined data management process for the company.